Impaired uptake of conjugated bile acids and hepatitis b virus pres1‐binding in na+‐taurocholate cotransporting polypeptide knockout mice. Issue 1 (8th May 2015) - Slijepcevic, Davor; Kaufman, Christina; Wichers, Catharina G.K.; Gilglioni, Eduardo H.; Lempp, Florian A.; Duijst, Suzanne; de Waart, Dirk R.; Oude Elferink, Ronald P.J.; Mier, Walter; Stieger, Bruno; Beuers, Ulrich; Urban, Stephan; et al.
<x xml:space="preserve">Abstract</x> The Na+‐taurocholate cotransporting polypeptide (NTCP) mediates uptake of conjugated bile acids (BAs) and is localized at the basolateral membrane of hepatocytes. It has recently been recognized as the receptor mediating hepatocyte‐specific entry of hepatitis B virus and hepatitis delta virus. Myrcludex B, a peptide inhibitor of hepatitis B virus entry, is assumed to specifically target NTCP. Here, we investigated BA transport and Myrcludex B binding in the first Slc10a1‐knockout mouse model (Slc10a1 encodes NTCP). Primary Slc10a1−/− hepatocytes showed absence of sodium‐dependent taurocholic acid uptake, whereas sodium‐independent taurocholic acid uptake was unchanged. In vivo, this was manifested as a decreased serum BA clearance in all knockout mice. In a subset of mice, NTCP deficiency resulted in markedly elevated total serum BA concentrations, mainly composed of conjugated BAs. The hypercholanemic phenotype was rapidly triggered by a diet supplemented with ursodeoxycholic acid. Biliary BA output remained intact, while fecal BA excretion was reduced in hypercholanemic Slc10a1−/− mice, explained by increased Asbt and Ostα/β expression. These mice further showed reduced Asbt expression in the kidney and increased renal BA excretion. Hepatic uptake of conjugated BAs was potentially affected by down‐regulation of OATP1A1 and up‐regulation of OATP1A4. Furthermore, sodium‐dependent taurocholic acid uptake was inhibited by Myrcludex B in wild‐type hepatocytes, while Slc10a1−/− hepatocytes were insensitive to Myrcludex B. Finally, positron emission tomography showed a complete abrogation of hepatic binding of labeled Myrcludex B in Slc10a1‐/‐ mice. Conclusion: The Slc10a1‐knockout mouse model supports the central role of NTCP in hepatic uptake of conjugated BAs and hepatitis B virus preS1/Myrcludex B binding in vivo; the NTCP‐independent hepatic BA uptake machinery maintains a (slower) enterohepatic circulation of BAs, although it is occasionally insufficient to clear BAs from the circulation. (Hepatology 2015;62:207–219)